Variation of Textural Attributes of S. Bartolomeu Pears at Maturation, Storage, and Drying - Guiné, Raquel (2012)
In the present work, the pears were dried in two different systems, both having the sun as the energy source: a solar stove with ventilation (ESAV) and a solar drier with natural convection (ESTV). The objectives of this work were to evaluate how instrumental textural properties changed during maturation, storing, and drying, as well as to compare the two different dry- ing methods. The results obtained allowed to see that drying affected the textural properties of pears in a way that hardness decreased very much during drying irrespective of the drying system used.